Female Infertility and Assisted Reproduction: Impact of Oxidative Stress - Agarwal, Ashok; Krajcir, Natalie; Chowdary, Hyndhavi; Gupta, Sajal (Current Women's Health Reviews, 2008)
Oxidative stress (OS) occurs with an overabundance of reactive oxygen species (ROS) generation and the inability of scavengers, i.e. antioxidants, to neutralize excessive loads of ROS. OS has a role in the etiopathologenesis of many factors causing natural infertility. Infertility is a problem of great magnitude affecting 6 million American women. The etiologies of unexplained infertility and recurrent pregnancy loss remain unclear and present a scientific challenge. Oxidative stress may be a piece in this puzzle. Although investigation of the exact mechanisms by which OS causes pathological processes affecting female fertility is ongoing, research has clearly shown that the redox state affects gametes, their interactions, and the resultant embryo. OS has adverse effects on assisted fertility including IVF/ICSI and in-vitro maturation. This article addresses the role of OS in female infertility, the effect it has on assisted reproductive techniques, and OS prevention strategies including the use of in-vivo and in-vitro antioxidant supplementation.
Keywords: in vitro fertilization